The genome sequence of the Currant Clearwing moth, Synanthedon tipuliformis (Clerck, 1759) - Boyes, D; Holland, PWH (F1000Research, 2023)
We present a genome assembly from an individual male Synanthedon tipuliformis (the Currant Clearwing; Arthropoda; Insecta; Lepidoptera; Sesiidae). The genome sequence is 295.8 megabases in span. Most of the assembly (99.98%) is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 27.05 kilobases in length. Gene annotation of this assembly on Ensembl identified 11,878 protein-coding genes.